Features of the prevention of intentional homicide by criminal police units - Хижняк, Євген Сергійович; Хижняк, Є. С.; Хижняк, Евгений Сергеевич; Khyzhniak, Yevhen S.; Ханькевич, Андрій Миколайович; Ханькевич, А. М.; Ханькевич, Андрей Николаевич; Khankevych, Andrii M.; Шаповаленко, Євген Володимирович; Шаповаленко, Є.В.; Шаповаленко, Евгений Владимирович; Shapovalenko, Yevhen V.; et al. (Editorial Primmate S. A. S., 2021)
The purpose of the article is to characterize the features of prevention of intentional homicide in terms of its implementation by criminal police units. Subject of research: The subject of research is the prevention of intentional homicide by criminal police units. Methodology: epistemological and legal method, methods of generalization and analysis, method of grouping, statistical, documentary and social survey methods, logical method are used in the course of the research. The results of the research: The article considers the main problems of determining the place and role of the victim in intentional encroachments on human life. Typical situations that lead to encroachment on life are analyzed, the role of the victim in each specific situation is determined. Practical implications: The main preventive measures to prevent intentional homicide by the police in general and criminal police units in particular are identified. Value / originality: The exceptional importance of intentional homicide preventing under modern conditions is substantiated.

Метою статті є характеристика особливостей профілактики умисним посяганням на життя людини в аспекті здійснення її підрозділами кримінальної поліції. Предмет дослідження: Предметом дослідження є профілактика умисних посягань на життя людини підрозділами кримінальної поліції. Методологія: діалектичний метод, метод аналізу та синтезу, логіко-семантичний метод, системний метод, метод класифікації та групування, індуктивний метод. Результати дослідження: У статті розглядаються основні проблеми визначення місця й ролі жертви в умисних посяганнях на життя людини. Аналізуються типові і ситуації, які призводять до посягання на життя, визначається роль жертви в кожній конкретній ситуації. Практичні наслідки: Визначені основні профілактичні заходи з попередження умисних вбивств поліцією загалом та підрозділами кримінальної поліції зокрема. Цінність / оригінальність: Обґруновується виключне значення профілактики умисних посягань на життя людини в сучасних умовах.
Khyzhniak Ye. Features of the prevention of intentional homicide by criminal police units / Ye. Khyzhniak, А. Khankevych, Ye. Shapovalenko, V. Shkelebei, Т. Yatsyk // Amazonia Investiga. – Vol. 10. - Issue 38. – Editorial Primmate S. A. S., 2021. – P. 212-218.
Keywords: prevention; intentional homicide; police; criminal police units; профілактика; умисні вбивства; поліція; підрозділи кримінальної поліції; Research Subject Categories::LAW/JURISPRUDENCE